Randomized controlled trials of mind–body interventions for posttraumatic stress disorder: a systematic review - Kaplan, Josh; Somohano, Vanessa C.; Zaccari, Belle; O’Neil, Maya E. (Frontiers in Psychology, 2024)
Mind-body interventions (MBIs) include mindfulness-based interventions (MiBIs), meditationand mantra-based interventions (MMIs), and movement-based interventions (MoBIs). These approaches have demonstrated preliminary efficacy in improving posttraumatic stress disorder (PTSD) symptoms. However, previous systematic reviews and meta-analyses have noted that this area of research is limited by inadequate comparator conditions, heterogeneity of measurement, and absence of objective outcome measures. For these reasons, an updated review of the highest-quality evidence available is warranted. We used the Agency for Healthcare Research and Quality (AHRQ)-funded evidence tables for the PTSD-Repository to identify relevant studies and assess risk of bias as follows: The search Electronic databases wasere conductedsearched between June 2018 and June 2022, and databases included PTSDpubs (formerly PILOTS), Ovid ® MEDLINE ® , Cochrane CENTRAL, Embase ® , the Cumulative Index to Nursing and Allied Health Literature (CINAHL ® ), SCOPUS, and PsycINFO ® . Twenty-six randomized controlled trials met our inclusion criteria. After identifying studies and retrieving risk of bias information from the PTSD-Repository evidence tables, we extracted additional data and synthesized the evidence. Strength of evidence was rated as low for MiBIs and MMIs, MIND-BODY RCTS FOR PTSD 2 largely due to contradicting results, inconsistent use of active versus passive comparators, and high risk of bias. Strength of evidence for MoBIs was rated as moderate due to individual studies consistently favoring the intervention and a relatively large number of studies and participants. Of the 26 included studies, only two included objective outcome measures. Implications for future MBI research and clinical applications for treating PTSD are discussed.